2020
DOI: 10.1038/s41524-020-00424-1
|View full text |Cite
|
Sign up to set email alerts
|

Auxetic two-dimensional transition metal selenides and halides

Abstract: Auxetic two-dimensional (2D) materials provide a promising platform for biomedicine, sensors, and many other applications at the nanoscale. In this work, utilizing a hypothesis-based data-driven approache, we identify multiple materials with remarkable in-plane auxetic behavior in a family of buckled monolayer 2D materials. These materials are transition metal selenides and transition metal halides with the stoichiometry MX (M = V, Cr, Mn, Fe, Co, Cu, Zn, Ag, and X = Se, Cl, Br, I). First-principles calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28] While in other cases, the auxetic behaviors are relevant to the electronic structures of 2D materials which determine the atomic interactions, rather than the geometry. [29][30][31][32] Strong auxetic effect will greatly improve the mechanical performance of materials, such as dentation resistance or hardness. However, the auxetic effects revealed in 2D materials remain very weak due to the low NPR values.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] While in other cases, the auxetic behaviors are relevant to the electronic structures of 2D materials which determine the atomic interactions, rather than the geometry. [29][30][31][32] Strong auxetic effect will greatly improve the mechanical performance of materials, such as dentation resistance or hardness. However, the auxetic effects revealed in 2D materials remain very weak due to the low NPR values.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, using the self-confined chemical vapor deposition approach, CuBr flakes with a wide band gap of 3.0 eV have been synthesized by Gong et al, which provides guidance for future synthesis of more 2D TMHals. Additionally, utilizing a structure data mining method based on the negative Poisson’s ratio (NPR) material discovery hypothesis, Pan et al recently identified a new set of 2D transition mental compounds, among which part of halides (CuCl, CuI, AgCl, AgBr, and AgI) exhibit exceptional mechanical behavior, originating primarily from the weak metal–metal interaction caused by electron occupation of antibonding states . Apart from electronic and magnetic properties, mechanical properties are also critical for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, utilizing a structure data mining method based on the negative Poisson's ratio (NPR) material discovery hypothesis, Pan et al recently identified a new set of 2D transition mental compounds, among which part of halides (CuCl, CuI, AgCl, AgBr, and AgI) exhibit exceptional mechanical behavior, originating primarily from the weak metal−metal interaction caused by electron occupation of antibonding states. 15 Apart from electronic and magnetic properties, mechanical properties are also critical for industrial applications. Considering this, the exploration of novel 2D TMHals with excellent mechanical properties has become a vital issue for their future roles in microelectromechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…In these calculations, the strain ε[110] is defined as ε The strain-induced NPR of this type of material can be explained by the competition between the Au-Au and Au-Te atomic interactions [93]. We can analyze the mechanism with the help of Fig.…”
Section: Mechanical Properties and Strain-induced Nprmentioning
confidence: 99%